PENGARUH GERAKAN LITERASI 15 MENIT TERHADAP PENINGKATAN NILAI AKM DENGAN VARIABEL MODERASI PEMAHAMAN TEKS BACAAN PADA SISWA SEKOLAH DASAR - Maryo Lukito; Beni Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low literacy achievement of Indonesian elementary school students, particularly in reading comprehension, has become a major challenge in improving Minimum Competency Assessment (AKM) outcomes. This study aimed to examine the effect of the 15-Minute Literacy Movement (Gerakan Literasi 15 Menit/GLM) on improving students' AKM scores, with reading comprehension serving as a moderating variable. The study employed a quantitative approach using an associative correlational design involving 154 elementary school students from the Northern Cluster (Dabin Utara), Kedungbanteng District. Data were collected through questionnaires, reading comprehension tests, and AKM literacy scores, and analyzed using Moderated Regression Analysis (MRA). The findings revealed that the implementation of the 15-Minute Literacy Movement had a positive and significant effect on students' AKM scores (β = 1.125; p < 0.001). Reading comprehension also had a significant positive effect on AKM achievement (β = 0.485; p = 0.002). Furthermore, reading comprehension significantly moderated the relationship between the 15-Minute Literacy Movement and AKM scores (β = 0.312; p = 0.009), indicating that the effectiveness of the literacy program depends on students' initial reading comprehension abilities. These findings suggest that literacy activities should not merely focus on reading habits but also emphasize meaningful comprehension through interactive teaching strategies and appropriate reading materials. The study provides empirical evidence for strengthening school literacy policies to improve students' literacy competencies and AKM performance.